CHALLENGES FACING CONTRACTORS IN THE EXECUTION OF PUBLIC BUILDING PROJECTS AND THEIR IMPACT ON PERFORMANCE - Emmanuel Omopariola; Jacob Olusegun Ilori; Abimbola Olukemi Windapo (Journal of Construction Project Management and Innovation)
In the Nigerian construction industry, many challenges are being faced by the contractors in the execution of public building projects; these challenges have not been investigated properly and their impacts on cost, time, quality and client satisfaction have not been thouroughly examined. Therefore, this study evaluates the challenges facing contractors in the implementation of public building projects in Nigeria and whether these impact on performance. The objective of the study is to suggest strategies for improved project performance. A quantitative research approach was adopted for the study, employing a cross-sectional survey of 128 construction professionals who are directly involved in the execution of public building projects in Nigeria. Questionnaires were self-administered to the respondents and 79 responses were retrieved and found valid for analysis, representing a response rate of 62%. The data obtained were analysed using a mean item score and regression analysis. The findings indicate that difficulties in obtaining financial aid, delayed payment by the client and poor leadership skills of the project manager are topmost challenges facing the contractor in the execution of public building projects. It is concluded that these challenges have significant impacts on the performance of the projects. The challenges can be  managed through prompt payment by clients, proper planning and scheduling of the project, and fixing a ceiling on the interest on funds borrowed. The study recommends that clients should timely honour interim certificates, and avoid too many variations. Contractors are advised to raise finance from the bank to solve the immediate cash flow problem, and to repay such loans as soon as they receive payment from the clients.